Analysıs of Performance of Indıan Companıes ın Retaıl Industry - Sai Shruthi Vaigunta Moorthy, Dr. Chetan Panse (International Journal of Advanced Science and Technology, 2020)
Retail sector is the backbone of any community. It provides the basic necessity of human beings or help them process it, i.e. food and many other products like apparel, electronics and home products. The major companies in the global retail industry include, Walmart Inc, Costco, Carrefour, Amazon.com Inc, Target Corp, The Kroger Co, etc and the major players in the Indian market include Avenue supermarts limited, Shoppers stop Limited, Future retail Limited, Reliance retail, etc. In developing countries like India, this sector is developing but at a dynamic rate. Retailing contributes to about 10 percent of the gross domestic product and 8 percent of the total employment base in the country. Hence the main purpose of this study is to analyse the performance of some Indian companies in the retail industry by comparing them. The companies taken for analysing are Reliance retail, Trent, Avenue supermarts Limited and Future retail Limited. This would help us understand the retail industry as a whole. The tool used for the comparison is Data envelopment analysis. It is a linear programming tool that measures the relative efficiency of one by comparing with other similar units that perform similar functions. The input variable used for the comparison is Inventory turnover ratio. For conducting this study, secondary data was extracted from Prowess Database of CMIE for ten year period. The input parameters considered were Return on assets (ROA), Return on Equity (ROE) and Net profit margin which act as indicators of profitability of an organization and liquidity parameters like quick ratio, current ratio. Analysing the financial performance of the above stated organizations by using the mentioned financial parameters